Effect of different ages of a rehabilitated forest on selected physico-chemical properties - Murugayah, Rajeswari; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Abstract: Problem statement: This research was important because of still lack of information about rehabilitated tropical forest age effect on infiltration rate. The objectives of this study were to determine the influence of age of forest on soil water infiltration rate and to evaluate the influence of forest age on the relationship between water infiltration rate, soil organic matter and soil texture. Approach: This study was conducted under a rehabilitated forest at Bukit Nyabau (University Putra Malaysia Bintulu Campus, UPMKB) Forest. Soil organic matter, soil texture and infiltration rate were investigated in randomly selected blocks representing different age classes, namely two, four, six, eight and ten years. Results: The results indicated that 2, 4, 6 and 8 year old forest were not significantly different in organic matter content with the mean of 8.10+2.75, 9.32+3.50, 9.55+1.71 and 8.10+2.75% respectively. Besides, 10 year forest showed no significant differences compared with two and eight year forests. Soil texture for all the forests was sandy loam, except for the 4 year old forest which was a sandy clay loam. The lowest value of sand content was observed in four year forest. However, the clay content in this forest was statistically the highest compared with 2, 4, 8 and 10 year old forest. The infiltration rate of 6 years old forest was significantly greater in soil water infiltration rate with the mean of 5.0±0.02 mm m-1, compared with 2, 4, 8 and 10 years old forest with the means of 2.6±0.02, 4.2±0.03, 3.6±0.03 and 3.5±0.03 mm m-1 respectively. Eight and 10 year old forests showed no significant differences in terms of soil water infiltration rate and the lowest value of water infiltration rate was observed in the two year old forest. Conclusion: From the results, it can be concluded that the soil water infiltration rate in the forest is mainly influenced by soil texture and organic matter content, but not by forest age. However, the effect of soil texture was significant compared to organic matter which facilitates water movement into soil. Soil texture with higher percentage of sand and lower percentage of clay had higher infiltration rate.